Adoption of System of Rice Intensification(SRI) in Kerala - Shanmugasundaram, B. (Indian Journal of Extension Education, 2015)
A field study was undertaken to analyse the nature and constraints in adoption of System of rice Intensification in  Kerala . An ex-post-facto research design was followed for the study conducted in selected three districts of Kerala. Atotal  of 200 adopter categories representing small , medium and large farmers were taken as sample. The sample categories  under the study comprises the beneficiaries of System of Rice Intensification(SRI)schemes implemented under the  central and state governmental schemes.Constraints under the seven major core components of SRI viz., single seedling  planting, wide spacing, water management, Mat nursery preparation, Levelling, weed management and Application of  organic Manures werestudied.Needed strategies for upscaling of SRI include Farmer to farmer extension, Organisation  of farm field school, incentives for SRI, Mechanisation, regulation of water flow, availability of SRI tools and information  support, awareness campaign and involvement of SHGs .
Keywords: Adoption; system of rice intensification; constraints; strategies; rice farmers